Does human pedestrian behaviour influence risk assessment in a successful mammal urban adapter? - Bateman, Bill; Fleming, P. (Wiley-Blackwell, 2014)
Optimal escape theory predicts that animals should moderate their flight responses according to the level of risk represented by a potential predator. This theory should apply even when organisms are habituated to disturbance, and how animals respond to human presence is likely to determine their success exploiting urban habitats. Therefore, urban animals should be sensitive to cues that inform them about levels of risk, allowing them to reduce costs by not overreacting to innocuous stimuli, while ensuring that they are nevertheless reactive to genuinely threatening stimuli. We tested this at a highly urbanized site in New York City, where eastern grey squirrels appear to pay little attention to humans. Squirrels were approached tangentially on a trajectory that took the observer within ~2 m of them and we measured alert distance, flight initiation distance (FID), and distance fled for each focal individual. Squirrels showed little sign of being alerted to the pedestrian if he remained on the footpath and did not look at them (only 5% of individuals moved away), but 90% of squirrels moved away, with longer FID and flight distance, when approached by a pedestrian that moved off the footpaths and looked at them. Squirrels therefore modulate their reactions when pedestrians behave in a predictable manner (i.e. remaining on the footpaths) and are also sensitive to the direction of attention of humans, reducing unnecessary responses, and are thereby likely to be increasing their ability to persist in this urban environment. Previous studies have emphasized the behavioural plasticity of successful urban wildlife species. In this study, we emphasize the importance of disturbance monitoring by successful urban exploiters, allowing them to vary their behavioural responses according to the level of risk to which they are exposed.